VPH-5 Competency of Meat Inspectors (keurmaster) and Level of Training Needs Based on the Standard of Working Competency - Dwi Windiana (Hemera Zoa, 2018)
A training program is a series of stages of training implementation that includes the analysis of training needs, the formulation of training needs, curriculum and syllabus, training patterns, training methodologies, modules and/or teaching materials as well as evaluation of learning to ensure the achievement of learning outcomes, while the training needs analysis is the activities to analyze the position/job and identify training needs (Ministry of Agriculture, 2018). Meat inspectors (keurmaster) are persons who assist the Veterinarians that are technical in charge of veterinary public health surveillance at the slaughter houses (Ministry of Agriculture, 2010).